A questão do Feudalismo no Brasil: um debate político - Mendes, Claudinei Magno Magre [UNESP] (My University, 2013)
In this article, we examine the procedure of Brazilian historiography about the debate between Caio Prado Jr. and the Brazilian Communist Party, especially with regard to the relationships of feudal or semi-feudal nature. The historiography put them on opposite sides, considering the intellectual from Sao Paulo from a positive outlook, while the Communist Party is considered from a negative one. However, although distinct, their interpretations of the history of the Brazil make them close in regards to the question of socialism, in that they postpone it to the remote future. Thus, by adopting the procedure of the opposition between both, the historiography fails to consider what really distinguished them.

Neste texto examinamos o procedimento da historiografia brasileira acerca do debate entre Caio Prado Jr. e o Partido Comunista Brasileiro, principalmente no que diz respeito às relações de natureza feudal ou semifeudal. A historiografia os contrapõe, considerando o intelectual paulista de um prisma positivo, ao passo que o Partido Comunista é considerado de uma perspectiva negativa. Todavia, ainda que distintas, suas interpretações da história do Brasil os aproximam no que diz respeito à questão do socialismo na medida em que elas o postergam para um futuro remoto. Assim, ao adotar como procedimento a contraposição entre ambos, a historiografia deixa de considerar aquilo que realmente os distinguia.
Keywords: Historiography; Feudalism; Brazilian Communist Party; Historiografia; Feudalismo; Caio Prado Júnior; Partido Comunista Brasileiro